Killing Fields: Environment, Agency, and the Fascist Conquest of Colonial Libya - Pergher, Roberta (2021)
The article seeks to reflect on the question of "nature’s agency" in histories of violence. It thus revisits the choices and outcomes of Fascist policy in Libya by foregrounding the colony’s ecology. The determination to win a war on inhospitable terrain led to the regime’s decision to set up concentration camps for Bedouin tribes and their herds in the desert-like and semiarid areas of Cyrenaica, which in turn had a murderous effect on humans and animals. From there, the article moves on to the second phase of Italian conquest, when the defeat of the anticolonial resistance turned into a "conquest of nature", with the agricultural reclamation of the highlands of Cyrenaica for Italian settlers. These agricultural centers and their people, which might at first sight seem bucolic and benign, were just as injurious to the Bedouin ecology predating the Italian occupation as were the concentration camps. The conclusion ponders the moral imperatives in writing histories of Fascist violence and the openings for environmental history.